Igniting an Agenda for Health Promotion for Women: Critical Perspectives, Evidence-based Practice, and Innovative Knowledge Translation - Pederson, Ann (Can J Public Health, 2010)
Health promotion is a set of strategies for positively influencing health through a range of individual, community-based, and population interventions. Despite international recognition that gender is a primary determinant of health and that gender roles can negatively affect health, the health promotion field has not yet articulated how to integrate gender theoretically or practically into its vision. For example, interventions often fail to critically consider women’s or men’s diverse social locations, gender-based power relations, or sex-based differences in health status. Yet without such analyses, interventions can result in the accommodation or exploitation of gender relations that disadvantage women and compromise their health. In this paper, we seek to ignite an agenda for health promotion for women. We discuss the need for a conceptual framework that includes a sex-gender-diversity analysis and critically considers ‘what counts’ as health promotion to guide the development and implementation of evidence-based practice. We also consider how innovative knowledge translation practices, technology developments and action research can advance this agenda in ways that foster the participation of a wide range of stakeholders.